“English without Borders”: English teaching based on a sociocultural perspective towards an autonomous learning - Nicolaides, Christine Siqueira; Matos, Anderson Silva (Revista Leitura, 2016)
Due to the low proficiency of the English language among Brazilian students at the tertiary level, the "Inglês sem Fronteiras Program - Isf was established by the Brazilian Government aiming to prepare undergraduate and graduate students to take international proficiency tests so that they can take part on international mobility programs. As applied linguists though we see language as social practice and raise questions such as which should be the real purpose of learning English or any other foreign/additional language (other than only training students for proficiency tests), and also how this new knowledge could actually benefit students´ communities of practice (LAVE & WENGER, 1991) developing (or not) what is called sociocultural autonomy (OXFORD, 2003), instead of focusing solely in the individual perspective towards learner autonomy. Therefore, this study raises some insights based on theoretical ground about sociocultural autonomy and brings some research data to illustrate it, which were generated during classes of the IsF Program. Our data shows that it is possible to create a class environment in which sociocultural autonomy may be stimulated through teacher´s motivation and peer collaboration. DOI: 10.28998/2317-9945.2015v2n56p173-193